FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK BUMI DAN BANGUNAN DI KOTA PEKANBARU TAHUN 2013-2018 - Doly Tasda; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the factors that affect land and building tax revenue in Pekanbaru City. This research uses a qualitative method with a descriptive analysis case study. Data collection techniques used through interviews as primary data and field search as secondary data.          The concept of the theory used by researchers is the driving factors and inhibitors of tax revenue indicators, namely, Economic Growth, Number of Population and Awareness of taxpayers. This research uses qualitative research methods, with descriptive data review. In collecting data, researchers used interview and documentation techniques.          The results of this study are that Economic Growth and Population Number affect land and building tax receipts in Pekanbaru City in 2013-2018. If it can be realized it will certainly be a potential source of revenue. And also the inhibiting factor in receiving land and building tax is the lack of awareness and compliance of taxpayers in paying taxes, so that the achievement of the targets set is not achieved or optimal. Then this is the cause of the non-optimal revenue from land and building tax in Pekanbaru City. Keywords: Economic Growth, Population, Awareness of Land and Building                                  Taxpayers.